Analysis of SGLT2 Inhibitor Therapy and Other Potential Risk Factors for the Development of Bacteremia in Patients With Urosepsis. (April 2022) - Covington, Elizabeth W.; Slaten, Kelly; Harnden, Adam
Background: Risk factors for the development of bacteremia in patients with urosepsis are not well-defined in the current literature.Objective: To assess potential risk factors, including receipt of SGLT2 inhibitor therapy (SGLT2-I), for the development of bacteremia in patients with urosepsis.Methods: A retrospective case control study was performed on patients admitted to a community hospital. Patients were included if they had a positive urine culture and met criteria for urosepsis. Exclusion criteria included proven source of infection outside of the urogenital tract, age less than or equal to 18 years old, and pregnancy. Included patients were placed into 1 of 2 groups: bacteremia or non-bacteremia. The primary endpoint was the percentage of patients taking an SGLT2-I in the bacteremia versus the non-bacteremia group. Secondary endpoints included an assessment of potential risk factors for the development of bacteremia in patients with urosepsis via univariate and multivariate regression analysis and comparison of clinical outcomes in patients receiving SGLT2-I prior to admission versus those not receiving SGLT2-I.Results: There was no difference in the proportion of patients within the bacteremia and non-bacteremia groups who were receiving an SGLT2-I (12% vs. 19%, P = 0.277). Binary multivariate regression analysis identified 2 variables associated with increased risk of bacteremia: male gender and cirrhosis.Conclusion: Within this study, there was no difference in the proportion of patients receiving an SGLT2-I in bacteremia and non-bacteremia groups. Potential risk factors for the development of bacteremia identified included male gender and cirrhosis. However, results from our study should be confirmed in larger scale studies.